Predicting Fear of Negative Evaluation: The Roles of Cognitive-Behavioral Avoidance and Emotional Well-being - Wei , Jing; Zhang , Yang (Journal of Assessment and Research in Applied Counseling (JARAC), 2025)
Objective: The study aimed to investigate the relationships between fear of negative evaluation (FNE), cognitive-behavioral avoidance, and emotional well-being. Methods and Materials: A cross-sectional design was utilized, with 298 participants recruited through convenience sampling. The Fear of Negative Evaluation Scale (FNE), Cognitive-Behavioral Avoidance Scale (CBAS), and Positive and Negative Affect Schedule (PANAS) were administered to measure the variables. Data were analyzed using Pearson correlation to assess relationships between variables and multiple regression to evaluate the predictive power of Cognitive-Behavioral Avoidance and Emotional Well-being on FNE. All analyses were conducted using SPSS version 27. Findings: Multiple regression analysis revealed that Cognitive-Behavioral Avoidance (B = 0.67, p < 0.001) and Emotional Well-being (B = -0.45, p < 0.001) significantly predicted FNE, explaining 42% of the variance (R² = 0.42). Conclusion: The study confirmed that Cognitive-Behavioral Avoidance and Emotional Well-being are significant predictors of Fear of Negative Evaluation. These findings suggest that interventions targeting avoidance behaviors and enhancing emotional well-being could effectively reduce FNE and related social anxiety symptoms. Future research should employ longitudinal designs and explore additional psychological mechanisms influencing these relationships.